A formação de professores nos cursos de licenciatura: um estudo de caso sobre o curso de ciências biológicas da Universidade Federal de Minas Gerais - Julio Emilio Diniz Pereira (1996)
This work describes and analyses the present situation of graduation courses on formation of teachers in Brazilian universities (in Brazil these courses are called licenciaturas) through a case study of the Biologic Science Course, a graduation course of the Federal University of Minas Gerais (UFMG). In this course, there are two kinds of degree: the Bacharelado; which is a course aimed at the graduation of researchers; and the licenciatura which is concerned about the formation of primary and high school teachers. The axis of all the discussion is the relation between teaching" and research" in the university and its effects on the licenciatura courses". The present situation of these courses is shown through two analyses: an analysis of the educational bibliography on formation/instruction of teachers in Brazil and, more specifically, about the licenciatura courses: and an analysis of the collected data at UFMG and in the Biological Science Course. in the data, the main points analysed are the differences and similarities in the profiles of students and professors involved in the two kinds of degree. After that, the present condition of the licenciaturas" is to be explained through an analysis of the constitution of the Biological Science champ (according to the definition of Pierre Bourdieu) at UFMG, from its origin until the present. The study of the representations about teaching "and research" by professors and students of this course is also used in order to better understand today's reality. Finally, it could de said that this case study" tries to detect the main problems faced by the licenciaturas courses" in the university identifying the reason why the alternatives for a change in this framework should extrapolate the insistent and not very efficient modifications on the school curriculum, recurrently proposed in order to improve the courses on instruction and formation of teachers.